Intraductal placement of a fully covered metal stent with a long string for distal malignant biliary obstruction without endoscopic sphincterotomy: Prospective multi‐center feasibility study. Issue 6 (12th March 2020) - Inoue, Tadahisa; Suzuki, Yuta; Okumura, Fumihiro; Naitoh, Itaru; Sano, Hitoshi; Ibusuki, Mayu; Kitano, Rena; Kobayashi, Yuji; Ito, Kiyoaki; Yoneda, Masashi
Abstract : Background: Stent migration and sludge clogging are characteristic problems in biliary covered self‐expandable metal stent (SEMS) placement. Intraductal placement without endoscopic sphincterotomy (ES) may help reduce their occurrence. We examined the feasibility of intraductal placement of a covered SEMS with a long string without ES in patients with unresectable distal malignant biliary obstruction (MBO). Methods: This was a prospective multi‐center observational study. Forty patients with distal MBO were enrolled between July 2016 and August 2018. We evaluated recurrent biliary obstruction (RBO), adverse events other than RBO, and reintervention associated with intraductal placement without ES. Results: Both technical and functional success rates were 100% (40/40). The rate of adverse events other than RBO was 5% (2/40). The RBO rate was 33% (13/40), and the median time to RBO was 339 days. RBO was mainly caused by overgrowth on the papillary side, occurring in six patients; all such patients had pancreatic cancer and a distance between the papilla and the stricture of ≤20 mm. Other causes were overgrowth at the hepatic side in two patients and sludge in five patients. No instances of stent migration occurred. Success rates of endoscopic transpapillary reintervention and stent removal using the string were 92% (12/13) and 77% (10/13), respectively. Conclusions: Intraductal placement without ES using a long‐stringed covered SEMS is a promising option for distal MBO. Since overgrowth on the papillary side is frequent, the procedure should be avoided in patients with short distances between the stricture and the papilla. (Clinical Trial Registry: UMIN000023370)